The purposes and objectives of socialistic modernization in Deng Xiaoping's comprehension (Journal of Oriental Studies, 2016)
in the article are considered the purposes and objectives of socialistic modernization in Deng Xiaoping's comprehension.
Keywords: Deng Xiaoping; China; socialistic modernization